Involvement of the cerebellum in Parkinson disease and dementia with Lewy bodies. Issue 6 (2nd June 2017) - Seidel, Kay; Bouzrou, Mohamed; Heidemann, Nina; Krüger, Rejko; Schöls, Ludger; den Dunnen, Wilfred F. A.; Korf, Horst‐Werner; Rüb, Udo
Abstract : Brains from patients with Parkinson disease or dementia with Lewy bodies show aggregation of alpha‐synuclein in precerebellar brainstem structures. Furthermore, patients exhibit resting tremor, unstable gait, and impaired balance, which may be associated with cerebellar dysfunction. Therefore, we screened the cerebella of 12 patients with alpha‐synucleinopathies for neuropathological changes. Cerebellar nuclei and neighboring white matter displayed numerous aggregates, whereas lobules were mildly affected. Cerebellar aggregation pathology may suggest a prionlike spread originating from affected precerebellar structures, and the high homogeneity between patients with dementia with Lewy bodies and Parkinson disease shows that both diseases likely belong to the same neuropathological spectrum. Ann Neurol 2017;81:898–903